1992
DOI: 10.1007/bf00185463
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of muscle regeneration in the rat gastrocnemius muscle by low energy laser irradiation

Abstract: The effect of low-energy laser (He-Ne) irradiation on the rate of skeletal muscle regeneration after partial excision of the rat gastrocnemius muscle was studied using quantitative histological morphometric methods. The injured zones of the experimental rats were subjected to direct He-Ne laser (632.8 nm wavelength) irradiation (6.0 mW for 2.3 min) immediately following injury and once daily thereafter for 5 days. Muscles that were injured as above and subjected to red or room light irradiation served as a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 18 publications
5
59
1
6
Order By: Relevance
“…In the present study, necrotic fibres were removed faster in groups II (LELI) and IV (coenzyme Q10 and vitamin E), compared to other evaluated groups, which was probably associated with increased activity of phagocytic cells. This confirmed the results obtained by other authors, demonstrating the positive impact of the LELI on muscle regeneration by increasing the metabolic activity of macrophages (Weiss and Oron 1992, Bibikova and Oron 1994, Podbielski et al 2006). On the other hand, LELI has an ability to modulate the inflammatory process and to optimize tissue repair by inhibiting some inflammatory mediators: prostaglandin, arachidonic acid and cyclooxygenase-2 (Rennó et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, necrotic fibres were removed faster in groups II (LELI) and IV (coenzyme Q10 and vitamin E), compared to other evaluated groups, which was probably associated with increased activity of phagocytic cells. This confirmed the results obtained by other authors, demonstrating the positive impact of the LELI on muscle regeneration by increasing the metabolic activity of macrophages (Weiss and Oron 1992, Bibikova and Oron 1994, Podbielski et al 2006). On the other hand, LELI has an ability to modulate the inflammatory process and to optimize tissue repair by inhibiting some inflammatory mediators: prostaglandin, arachidonic acid and cyclooxygenase-2 (Rennó et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that muscle regeneration, in vivo as well as in vitro, becomes more effective when treated with low intensity laser 6,7 . It has been demonstrated 8,9 that lasers operating at different wavelengths activate the macrophages to release factors that stimulate fibroblast proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Photobiomodulation effects of Low-level light irradiation (LLLI) on regeneration have been reported in skin [1] [2], nerve [3], skeletal muscle tissues [4] and bone [5]. LLLI can be used as a efficiently tool for the preconditioning of bone marrow mesenchymal stem cells (MSCs), which derived from bone marrow and received wildly attentions in regeneration medicine.…”
Section: Introductionmentioning
confidence: 99%